Comparative study of cell alterations in oral lichen planus and epidermoid carcinoma of the mouth mucosa - De Sousa, Fernando Augusto Cervantes Garcia; Paradella, Thaís Cachuté; Brandão, Adriana Aigotti Haberbeck [UNESP]; Rosa, Luiz Eduardo Blunter [UNESP] (Elsevier, 2009)
Currently, much is discussed regarding the pre-malignant nature of mouth mucosa lichen planus. Aim: The present study aims at analyzing the alterations found in the epithelial cells present in the oral cavity lichen planus, comparing them to those found in epidermoid carcinoma. Materials and Methods: Histological cross-sections of oral lichen planus and epidermoid carcinoma, dyed by hematoxylineosin, were analyzed through light microscopy. Result: the most frequently found alterations in oral lichen planus were: an increase in the nucleus/cytoplasm relation (93-33%), nucleus membrane thickness (86.67%) and bi-nucleus or multinucleous (86.67%). The Student t test (alpha=5%) revealed a statistically significant difference between the average number of cell alterations in oral lichen planus (5.87±1.57) and in epidermoid carcinoma (7.60±1.81). As to fhe types of alterations, the chi-squared test also revealed statistically significant differences among the lesions assessed in relation to the following cell alterations: nuclear excess chromatism, atypical mitoses, cellular pleomorphism and abnormal cell differentiation (p<0.05). Conclusion: Despite the fact that in some cases, some padiologists may make mistakes in the histopathological diagnosis of oral lichen planus, the results obtained in this study show that the alterations present in oral lichen planus differ considerably from those seen in epidermoid carcinoma, thus showing how distinct these two diseases are.
Keywords: Epidermoid carcinoma; Lichen planus; Mouth mucosa